The output current ripple and the dynamic characteristics of an 18-pulse thyristor rectifier, designed for the electromagnet power supply - Vukic, Vladimir Đ. (Proceedings, Electrical engineering institute "Nikola Tesla", 2018)
The aim of this paper is to analyse the possibility of applying a topology of an eighteen-pulse thyristor rectifier for the electromagnet power supply. The scope was to determine if the proposed rectifier topology, with the two input interphase transformers, as well as the output one, can work with an output current ripple being less than 100 ppm, with the acceptable dynamic characteristics of the voltage controller. Using the computer simulation, it has been found that, with a medium output filter capacitor and distinctively non-symmetric input parameters, the rectifier can work with an output current of approximately 80 ppm of the DC component. If the input phase voltages were equalized, the effective value of the output current ripple could be reduced down to 17 ppm. In both cases, satisfactory dynamic characteristics of the voltage controller have been achieved. The dominant influence on the output current filtering had the output interphase transformer magnetization inductance, as well as the capacitance of the filter capacitor. Increase of their values leads to better filtering of the output current, but also to a significant deterioration of the AC/DC converter dynamic characteristics. Measures for harmonization of the output low-pass filter characteristics and the PI voltage regulator parameters are proposed.
Keywords: thyristor bridge; 18-pulse rectifier; electromagnet; current ripple; computer simulation